2022
DOI: 10.1101/2022.02.07.22270654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choroid plexus volume predicts expansion of chronic lesions and brain atrophy

Abstract: Background and Objectives: The expansion of long-standing multiple sclerosis (MS) lesions and an enlargement of choroid plexus are linked to chronic inflammation and microglial activation. In the current study, we investigated the association between plexus volume and subsequent lesion expansion in patients with relapsing remitting MS. Methods: Pre- and post-gadolinium 3D-T1, 3D FLAIR and diffusion tensor images were acquired from 49 patients with relapsing-remitting MS. Choroid plexus volume and lesion activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…(Fleischer et al 2021) (Manouchehri and Stüve 2021) (V. A. Ricigliano et al 2021) (S. Klistorner et al 2022). We recently reported that volume of CP predicts subsequent expansion of chronic periventricular MS lesions and is associated tissue damage within and outside of chronic lesions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…(Fleischer et al 2021) (Manouchehri and Stüve 2021) (V. A. Ricigliano et al 2021) (S. Klistorner et al 2022). We recently reported that volume of CP predicts subsequent expansion of chronic periventricular MS lesions and is associated tissue damage within and outside of chronic lesions.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the volume of the CP was linked to traditional measures of disease activity, including relapse rate and the number of enhancing lesions and expansion of chronic lesions (Fleischer et al 2021) (V. A. Ricigliano et al 2021) (Manouchehri and Stüve 2021) (S. Klistorner et al 2022).…”
Section: Introductionmentioning
confidence: 99%